The management of anticoagulation in patients undergoing therapeutic plasma exchange: A concise review. Issue 3 (26th October 2017) - Shunkwiler, Sara M.; Pham, Huy P.; Wool, Geoffrey; Ipe, Tina S.; Fang, Deanna C.; Biller, Elizabeth; Treml, Angela; Weiss, John; Baron, Beverly W.; Berg, Mary
Abstract : We surveyed multiple apheresis centers represented by the authors for their clinical approach to the management of anticoagulation issues during therapeutic plasma exchange (TPE). We present the results of their practices and a review of the pertinent literature. As plasma is removed during TPE, replacement with all or partial non‐plasma‐containing fluids (eg, 5% albumin) may lead to significant changes in hemostasis. These changes are amplified in patients who are receiving anticoagulation. We discuss various anticoagulants as well as the monitoring and adjustment of anticoagulation before, during, and after TPE. No single guideline can be applied, but rather, patients must be monitored individually, taking into account their often complex clinical conditions and medication profiles.